2009
DOI: 10.1080/03014220909510145
|View full text |Cite
|
Sign up to set email alerts
|

An updated checklist of helminth and protozoan parasites of terrestrial mammals in New Zealand

Abstract: A combined and updated checklist of helminth and protozoan parasites of terrestrial mammals in New Zealand is provided. This checklist, which is divided into two parts, includes a total of 301 parasites (151 nematodes, 27 cestodes, 8 trematodes, 2 acanthocephalans and 113 protozoans) from 37 hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 111 publications
1
17
0
Order By: Relevance
“…Nonetheless, little empirical evidence remains on the extent and nature of host-parasite coextinction. Although we have confirmed that several Eimeriidae species infested moa, as previously suggested by past evidence (8), we identified that some of these species may still occur in the extant kiwi, which was previously confirmed to host an unidentified Eimeria (54). This result perhaps is unsurprising, as some Eimeriidae species can infect a broad range of host taxa (55).…”
Section: Discussionsupporting
confidence: 86%
“…Nonetheless, little empirical evidence remains on the extent and nature of host-parasite coextinction. Although we have confirmed that several Eimeriidae species infested moa, as previously suggested by past evidence (8), we identified that some of these species may still occur in the extant kiwi, which was previously confirmed to host an unidentified Eimeria (54). This result perhaps is unsurprising, as some Eimeriidae species can infect a broad range of host taxa (55).…”
Section: Discussionsupporting
confidence: 86%
“…The alimentary tract of New Zealand horses is home to at least 27 species of helminth parasite; 26 nematodes and the one cestode, Anoplocephala perfoliata (McKenna 2009). Of the nematode species, half are small strongyle species (cyathostomins), of which little is known individually.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of information is a problem in parts of the world, such as New Zealand, without a long tradition in marine parasitology. Although records of adult trematodes and other parasites in New Zealand bird and fish hosts have been compiled (Hewitt & Hine 1972;Weekes 1982;McKenna 1998;Hine et al 2000), there is no similar synopsis of the occurrence of the same parasite species in their larval stages within invertebrates. Over the past several years, numerous studies have documented the presence of trematode parasites in New Zealand soft-sediment intertidal ecosystems, especially in the Otago region, South Island (e.g., Martorelli et al 2004Martorelli et al ,2006Leung et al 2009).…”
Section: Introductionmentioning
confidence: 99%